Pencantuman Label Halal dalam Produk Umkm Tauco Cianjur menurut Undang-Undang Jaminan Produk Halal sebagai Upaya Perlindungan Konsumen - Adinda Mutiara I; Neni Sri Imaniyati; Asep Hakim Zakiran (UNISBA Press, 2022)
Abstract. Law Number 8 of 1999 concerning Consumer Protection states that consumers have the right to comfort, a security and safety in consuming goods and or services. For Muslim consumers, safe goods or services are halal goods or services. The obligation to include halal products is stated in an article 4 of Law Number 33 of 2014 concerning to guarantee Halal Products. A survey conducted by Frontier shows that 82.6% of Muslim consumers want the inclusion of a halal label. Based on data from LPPOM MUI, the issuance of Halal Certification is relatively low. The Cianjur government has the “ Gerbang Marhamah” Concept, but there is still Cianjur MSME products that have not been certified halal, including Tauco Cianjur.The purpose of this study is to understand the responsibility of business actors for the inclusion of halal labels in Tauco Cianjur MSME products as an effort to protect consumers in terms of Law Number 33 of 2014 concerning Halal Product Guarantee and to understand the implementation of the inclusion of halal labels in Tauco Cianjur MSME products in terms of Law Number 33 of 2014 concerning a halal Product Guarantee. The researcher uses a normative juridical approach with descriptive analytical research specifications and uses primary and secondary data types. The data collection techniques used are a library and interview methods and data analysis methods using a qualitative analysis.The results of this study are the responsibility of business actors for the inclusion of halal labels as an effort to protect consumers in terms of Law Number 33 of 2014 concerning Halal Product Guarantees is absolute responsibility (Stick Liability) and uses the principle of a reverse liability. the implementation of the inclusion of halal labels in MSME products Tauco Cianjur in terms of Law Number 33 of 2014 concerning to Guaranteed Halal Products is not yet implemented as whole. Abstrak. Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen menyatakan konsumen berhak atas kenyamanan, keamanan, dan keselamatan dalam mengkonsumsi barang dan atau jasa. Bagi konsumen muslim, barang atau jasa yang aman adalah barang atau jasa yang halal. Kewajiban mencantumkan kehalalan produk tertera pada Pasal 4 Undang-Undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal. Survey yang dilakukan oleh frontier menunjukan 82,6 % konsumen muslim menghendaki pencantuman label halal. Berdasarkan data LPPOM MUI, penerbitan Sertifikasi Halal relative rendah. Pemerintah Cianjur memiliki Konsep Gerbang Marhamah, namun masih terdapat produk UMKM Cianjur yang belum bersertfikasi halal termasuk Tauco Cianjur. Tujuan penelitian ini adalah untuk memahami tanggung jawab pelaku usaha terhadap pencantuman label halal dalam produk UMKM Tauco Cianjur sebagai upaya pelindungan konsumen ditinjau dari Undang-Undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal serta untuk memahami implementasi pencantuman label halal dalam produk UMKM Tauco Cianjur ditinjau dari Undang-Undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal.Peneliti menggunakan metode pendekatan yuridis normative dengan spesifikasi penelitian deskriptif analitis dan menggunakan jenis data primer dan sekunder. Teknik pengumpulan data yang digunakan adalah metode kepustakaan dan wawancara serta metode analisis data menggunakan analisis kualitatif.Hasil penelitian ini adalah tanggung jawab pelaku usaha terhadap pencantuman label halal sebagai upaya pelindungan konsumen ditinjau dari Undang-Undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal adalah tanggung jawab mutlak (Stict Liability) dan menggunakan prinsip pertanggungjawaban terbalik. Implementasi pencantuman label halal dalam produk UMKM Tauco Cianjur ditinjau dari Undang-Undang Nomor 33 Tahun 2014 Tentang Jaminan Produk Halal adalah belum terimplementasi secara keseluruhan.